2011
DOI: 10.1111/j.1600-0722.2011.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel alterations in serotonin 2B receptor knockout mice

Abstract: The role of the serotonin 2B receptor (5-HT(2B) R) in enamel formation and mineralization was explored in adult 5HT(2B) R knockout (KO) mice compared with wild-type (WT) mice. In the molar, quantitative data obtained by micro-computed tomography imaging showed that the overall volume of the enamel layer was firmly reduced in KO mice. Defective mineralization was ascertained by energy-dispersive X-ray microanalysis. We also observed, using scanning electron microscopy, that parazones in the KO mice included two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In contrast, the incisor outer enamel with rods running parallel to the enamel surface might be less susceptible to the altered rod–interrod profile caused by truncated FAM83H and therefore exhibit a minor hypoplastic defect. Interestingly, mice with ablation of serotonin 2B receptor ( Htr2b null mice) have a similar molar phenotype of generally thinner enamel with surface roughness, and the enamel microstructure and rod profiles of Htr2b −/− molars were also abnormal (Dimitrova‐Nakov et al, ; Harichane et al, ). Although the alteration of the rod profiles of molar enamel was not well detailed, primarily due to the high complexity of molar enamel microstructure and a lack of standardized methodology for molar characterization, it was clearly indicated that enamel analysis of mutant genotypes based exclusively on incisor defects can be biased (Goldberg, Kellermann, Dimitrova‐Nakov, Harichane, & Baudry, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the incisor outer enamel with rods running parallel to the enamel surface might be less susceptible to the altered rod–interrod profile caused by truncated FAM83H and therefore exhibit a minor hypoplastic defect. Interestingly, mice with ablation of serotonin 2B receptor ( Htr2b null mice) have a similar molar phenotype of generally thinner enamel with surface roughness, and the enamel microstructure and rod profiles of Htr2b −/− molars were also abnormal (Dimitrova‐Nakov et al, ; Harichane et al, ). Although the alteration of the rod profiles of molar enamel was not well detailed, primarily due to the high complexity of molar enamel microstructure and a lack of standardized methodology for molar characterization, it was clearly indicated that enamel analysis of mutant genotypes based exclusively on incisor defects can be biased (Goldberg, Kellermann, Dimitrova‐Nakov, Harichane, & Baudry, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fixed 3 month-old control and cKO molars were used for SEM analysis. SEM samples were etched with 0.1% nitric acid three times for 10 sec each; rinsed in running tap water, and dried and sputter-coated with gold-palladium for SEM as described in [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In adult, this receptor controls tissue non-specific alkaline phosphatase (TNAP) activity (Baudry et al, 2010), and thereby bone mineralization (Collet et al, 2008). Inactivation of the 5HT 2B R [5HT 2B R knockout (KO) mice] disturbs enamel formation (Harichane et al, 2011; Dimitrova-Nakov et al, 2014). …”
Section: Differential Structural Enamel Alterations Between Incisors mentioning
confidence: 99%